Evaluation of the Feller-Buncher Moipu 400E for Energy Wood Harvesting - Christian Rottensteiner; Günter Affenzeller; Karl Stampfer (Croatian Journal of Forest Engineering, 2008)
Proper tending operations in young stands increase the quality of valuable roundwood and reduce the risk of stand damages caused by wind and snow-breaks, and infestation of bark beetles. When felling and extracting small diameter trees, costs often exceed the potential revenues. Mechanized thinning performed by using a forwarder mounted feller-buncher head could improve this cost-effectiveness. Atime study was carried out in a 35–40 year old Scots Pine–Oak dominated stand. Productivity and costs were investigated of a Timberjack 1110D forwarder equipped with the felling-bunching head Moipu 400E. Further objectives were to give practical recommendations for the system in the field. The harvesting productivity was 4.11 m3/PSH0 (effective working hour) or 3.16 m3/PSH15 with an average tree volume of 0.057m3, an average load volume of 3.71m³, and the average forwarding distance 89 m. The supply costs from forest to plant (felling, forwarding, chipping, and transportation) were 91.60 eur/PSH15 or 77.84 eur per oven dry ton. In Austria it is possible to achieve revenues of 78.00 eur per oven dry ton. Therefore it is possible to gain profit. The feller-buncher head Moipu 400E is best suited to cut Pine trees up to a maximum diameter at the butt of about 30 cm, and Oak and Beech up to 25 cm. In order to keep the felling- bunching costs at a reasonable level, mechanized harvesting should be done at sites where the average volume of removed trees is over 0.05 m³ per tree.